Feministic Analysis of the House of the Spirits - et. al., Tesia George, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Begun in the nineteenth and early twentieth centuries, the feministic theory has manifested in a variety of disciplines including literature. The House of The Spirits written by the Chilean author Isabel Allende in 1982 depicts the struggle faced by women of different classes in different generations. Although the novel spans about fifty years of the life of Esteban Trueba, it is the women around him during distinct phases of his life that bring life to the novel. This study explores the patterns of women subjected to distress and misery because of the male subjects around them. The second wave of feminism which lasted roughly two decades finds itself in the vicinity of the movement. It is no secret that the writer wanted to portray the veracity of the society with revolutionary and conventional women. The work also portrays how women empower the spirits of others of their gender around them. This study challenges the belief that exceptional women who are constrained in their families because of their gender endure more grief till they become the best version of themselves.